2006
DOI: 10.1111/j.1365-2990.2006.00729.x
|View full text |Cite
|
Sign up to set email alerts
|

Gelatinase B [matrix metalloproteinase (MMP)‐9] and collagenases (MMP‐8/‐13) are upregulated in cerebrospinal fluid during aseptic and bacterial meningitis in children

Abstract: We investigated the protein expression of gelatinases [matrix metalloproteinase (MMP)-2 and -9] and collagenases (MMP-8 and -13) in cerebrospinal fluid (CSF) from patients with bacterial (BM, n = 17) and aseptic (AM, n = 14) meningitis. In both, MMP-8 and -9 were increased in 100% of patients, whereas MMP-13 was detectable in 53% and 82% respectively. Three patients with clinical signs of meningitis, without CSF pleocytosis, scored positive for all three MMPs. MMP-8 appeared in two isoforms, granulocyte-type [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 51 publications
1
28
0
Order By: Relevance
“…The observation that inflammatory parameters, including cyto-/chemokine concentrations and MMP activity in the CSF, were reduced in animals treated with MMP inhibitors compared with control littermates is in agreement with the assumption that an overshooting inflammatory response contributes to the development of brain injury in BM [16,41,70]. During acute neuroinflammation, pharmacological inhibition of the released active forms of MMPs is a more targetspecific intervention compared with other adjuvant therapies, in other words, corticosteroids, which act by modulating the transcriptional regulation of multiple target genes [28,131].…”
Section: • • Inhibition Of Mmp And/or Tnf Activity Is An Experimentallysupporting
confidence: 84%
“…The observation that inflammatory parameters, including cyto-/chemokine concentrations and MMP activity in the CSF, were reduced in animals treated with MMP inhibitors compared with control littermates is in agreement with the assumption that an overshooting inflammatory response contributes to the development of brain injury in BM [16,41,70]. During acute neuroinflammation, pharmacological inhibition of the released active forms of MMPs is a more targetspecific intervention compared with other adjuvant therapies, in other words, corticosteroids, which act by modulating the transcriptional regulation of multiple target genes [28,131].…”
Section: • • Inhibition Of Mmp And/or Tnf Activity Is An Experimentallysupporting
confidence: 84%
“…Analysis from serial lumbar punctures [7] revealed that the concentration of MMPs in the cerebrospinal fluid are only partially correlated with the CSF leukocyte count. This suggests that invading immune cells are only partially responsible for the activity of MMPs in the CSF during meningitis; therefore, parenchymal cells may be another relevant source.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have provided converging evidence that MMPs play a key role in the pathogenesis of meningitis through their contribution to the breakdown of the BBB and the accumulation of blood-derived immune cells. Gelatinases (MMP-2 and MMP-9) are probably the most extensively studied MMPs in the context of the pathogenesis of meningitis [6][7][8]. However, the cellular sources of MMP activity in the CNS are not yet clear.…”
Section: Introductionmentioning
confidence: 99%
“…MMP activity is not restricted to the ECM, but extends to mechanisms of cellular signaling by activation and inactivation of cytokines, growth factors, and hormones, among others. 76 In the context of neurologic diseases, MMPs mediate blood-brain and blood-nerve barrier breakdown and parenchymal invasion of neural tissue by blood-derived immune cells, 39,40 which has been extensively studied in multiple sclerosis, 41,46 infectious meningitis, 36,37,43,47 and stroke. 48,57,66 -68 The broad coverage of the role of MMPs in diseases of the central nervous system (CNS) is contrasted by a relative paucity of publications dealing with their role in the pathology of the peripheral nervous system (PNS), such as in neuropathy and myopathy.…”
mentioning
confidence: 99%